Assessment of blood collection competency in phlebotomists: a survey study - Coşkun Cihan; Gümüş Alper; Uçar Kamil Taha; Düz Muhammet Emin; Yeşil Beyazıt Semih; Özkan Asibe; Çiftçi Karan Eda (Türk Biyokimya Dergisi)
Blood collection, one of the most frequently performed procedures in healthcare settings. The study aimed to develop a scale for phlebotomy procedures based on national phlebotomy guidelines and to assess the tendencies of phlebotomy personnel in certain blood collection practices.